Pre-Columbian fire regimes in lowland tropical rainforests of southeastern Peru - McMichael, C. H.; Correa-Metrio, A.; Bush, M. B. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
We document the fire history of the forests of a well-studied ecological research station (Los Amigos) in western Amazonia through soil charcoal analysis, and compare results with data from a nearby lake district known to have supported pre-Columbian human populations. We present novel methods of soil charcoal analysis that improve on its current limitations by accounting for variability in post-fire charcoal deposition, problematic age–depth relationships, and the presence of weathered or regionally-deposited charcoal particles that allow statistical comparisons of fire history characteristics between regions. The fire histories indicate that the research station experienced less intensive historical fire and pre-Columbian disturbance than the lake district. Dated charcoal particles indicated that while soil depth could not be used to predict fire age, fragments below 20 cm depth were generally older than 500 years. Frequent fires have not occurred in either region during the last 1000 years, but fire events in both regions were significantly synchronous from 1000 to 4000 cal. yr BP. The sampling design and methods that provide an ecologically and statistically valid avenue for comparing fire history characteristics between regions can be modified to suit other ecosystems. The results presented here establish confidence that the patterns and processes of the lowland tropical rainforests studied at Los Amigos are not affected by intense or recurrent historical fires. These data also suggest that forests of Madre de Dios, Peru are not post-successional remnants of a ‘cultural parkland’, as suggested by some Amazonian archeologists.
id: 2307

From ice age to modern: a record of landscape change in an Andean cloud forest - Valencia, B. G.; Urrego, D. H.; Silman, M. R.; Bush, M. B. (Journal of Biogeography, 2010)
Aim
id: 869; 639ND Times Cited:5 Cited References Count:63Y

A long history of cloud and forest migration from Lake Consuelo, Peru - Urrego, D. H.; Bush, M. B.; Silman, M. R. (Quaternary Research, 2010)
The complete paleoecological history from Lake Consuelo forest yields a record of ground-level cloud formation and changes in its lower altitudinal limit over the last 46,300 cal yr BP. The timing of early lake level fluctuations prior to 37,000 cal yr BP appears sensitive to North Atlantic temperature oscillations, corresponding to Dansgaard-Oeschger interstadials 11, 10 and 8 recorded in GISP2. After the LGM, the first hint of warming is recorded in Lake Consuelo at 22,000 call yr BP and agrees with other estimates for the region. The mid-Holocene (7400-5000 cal yr BP) was the period of highest rates of change and most significant reorganizations in the Consuelo forest. These community changes resulted from a regionally widespread dry period. Results from Lake Consuelo indicate that moisture availability, mediated through cloud cover, played the most significant role in ecological change in this system. Rates of past climate fluctuations never exceeded the forest capacity to accommodate change. Unfortunately, this might not be the case under predicted scenarios for the end of the current century. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 1903; 564VS Times Cited:8 Cited References Count:85Y

A 24,900-year paleolimnological history from the Peruvian Andes - Hillyer, R.; Valencia, B. G.; Bush, M. B.; Silman, M. R.; Steinitz-Kannan, M. (Quaternary Research, 2009)
id: 1902

Evolution and latitudinal diversity gradient: Speciation, extinction, and biogeography - Mittelbach, G. G.; Schemske, D. W.; Cornell, H. V.; Allen, A. P.; Brown, J. M.; Bush, M. B. (Ecology Letters, 2007)
id: 456

Holocene fire and occupation in Amazonia: Records from two lake districts - Bush, M. B.; Silman, M. R.; de Toledo, M. B.; Listopad, C. R. S.; Gosling, W. D.; Williams, C.; De Oliveira, P. E.; Krisel, C. (Philosophical Transactions of the Royal Society of London, 2007)
id: 454

A Mid-Holocene environmental change in Amazonian savannas - de Toledo, M. B.; Bush, M. B. (Journal of Biogeography, 2007)
id: 455

A regional study of Holocene climate change and human occupation in Peruvian Amazonia - Bush, M. B.; Listopad, M. C. S.; Silman, M. R. (Journal of Biogeography, 2007)
id: 453

Deglaciation and Holocene climate change in the western Peruvian Andes - Weng, C. Y.; Bush, M. B.; Curtis, J. H.; Kolata, A. L.; Dillehay, T. D.; Binford, M. W. (Quaternary Research, 2006)
Pollen, charcoal, magnetic susceptibility, and bulk density data provide the first paleoecological record spanning the last 33,000 years from the western cordillera of the Peruvian Andes. Sparse super-puna vegetation existed before 30,000 cat yr B.P. around Lake Compuerta (3950 m elevation), prior to a sedimentary hiatus that lasted until c. 16,200 cat yr B.P. When sedimentation resumed, a glacial foreland or super-puna flora is represented in which Polylepis was a significant element. Glacial outwash, marked by high sedimentary magnetic susceptibility, increased from c. 16,200 cat yr B.P. and reached a peak at c. 13,200 cat yr B.P. Between c. 12,500 cat yr B.P. and 10,000 cat yr B.P., magnetic susceptibility was reduced. Vegetation shifts suggest a cool dry time, consistent with regional descriptions of the Younger Dryas event. Deglaciation resumes by 10,000 cat yr B.P. and the last ice is lost from the catchnient at similar to 7500 cat yr B.P. During the early Holocene warm and dry period between 10,000 and 5500 cat yr B.P., Alnus expanded in downslope forests. Alnus declined in abundance at 5500 cat yr B.P. when wetter and cooler conditions returned and human activity intensified. Maize (Zea mays) pollen first occurred in the core at similar to 2600 cat yr B.P., indicating a minimum age for local agriculture. An increase in Alnus pollen abundance at similar to 1000 cat yr B.P. could be due to human activity or perhaps due to a regional climate change associated with cultural turnover elsewhere in the Andes at this time. (c) 2006 University of Washington. All rights reserved.
058upTimes Cited:27Cited References Count:55

A multiproxy palaeoecological record of Holocene lake sediments from the Rio Tapajos, eastern Amazonia - Irion, G.; Bush, M. B.; de Mello, J. A. N.; Stuben, D.; Neumann, T.; Muller, G.; De, J. O.; Junk, J. W. (Palaeogeography Palaeoclimatology Palaeoecology, 2006)
Two sediment cores up to 42 m in length were raised from the wide, deep, section of the lower Tapajos River, Amazonia, referred to as Lago Tapajos. These cores reveal a history of subtle environmental change that began with the formation of Lago Tapajos as sea level rose about 11,000 years ago. The sediments of the lake were deposited fairly quickly-at a rate of ca. 4 m per millennium and are uniformly fine grained, with low organic content. The fossil pollen record derived from these sediments reveals that forest surrounded this site throughout the Holocene. The largest change in the core took place between ca. 5500 and 4200 cal. years BP and reflects a transition from coarser to finer sediments. Coincident with the change in sediment is a slight transition in the pollen spectra with an increase in Poaceae abundance at the expense of the pioneer tree Cecropia cecropia. A tentative explanation is offered in which increased human activity, possibly spurred by climatic change, resulted in the formation of some local grasslands. However, despite the apparent actions of humans, there is no indication of basin-wide transformation of landscapes in this record. The Holocene persistence of forest as the dominant landscape matrix around Lago Tapajos is supported by low delta C-13 values and by the constant geochemistry and mineralogy of the lake sediments. (c) 2006 Elsevier B.V. All rights reserved.
097fbTimes Cited:40Cited References Count:78

The rise and fall of the refugial hypothesis - Bush, M. B.; De Oliveira, P. E. (Biota Neotropica, 2006)
id: 457

A 17,000 year history of Andean climatic and vegetation change from Laguna de Chochos, Peru - Bush, M. B.; Hansen, B. C. S.; Rodbell, D. T.; Seltzer, G. O.; Young, K. R.; Leon, B.; Abbott, M. B.; Silman, M. R.; Gosling, W. D. (Journal of Quaternary Science, 2005)
The manifestation of major climatic events such as the timing of deglaciation and whether, or not, the Younger Dryas affected Andean systems has garnered considerable recent attention. Even the Holocene is rapidly emerging as a time of considerable interest in Neotropical palaeoclimatology and palaeoecology. The Holocene of the Neotropics is now revealed as a time of some temperature change with precipitation:evaporation ratios fluctuating markedly. Major changes in lake level, ice-accumulation, and vegetation are indicative of changes both in precipitation and temperature regimes. Although global-scale forcing mechanisms may underlie some of these changes, e.g. the precessional rhythm, other variability appears to be localised. In a record from near the upper forest limit of the eastern Peruvian Andes, pollen, charcoal, and sedimentary data suggest that the deglaciational period from ca. 17 000 to ca. 11 500 cal. yr BP was a period of rapid climatic oscillations, set against an overall trend of warming. A warm-dry event is evident between ca. 9500 and ca. 7300 cal. yr BP, and comparisons with other regional archives suggest that it was regional in scale. A ca. 1500-yr periodicity in the magnetic susceptibility data is evident between 12 000 and 6000 cal. yr BP, reaching a peak intensity during the dry event. A weaker oscillation with a 500–600-yr periodicity is present throughout much of the Holocene. The uppermost sample of the pollen analysis reveals deforestation as modern human land use simplified the landscape.
id: 1015

The last glacial maximum: stability and change in an Andean cloud forest - Urrego, D. H.; Silman, M. R.; Bush, M. B. (Journal of Quaternary Science, 2005)
id: 458

48,000 years of climate and forest change from a biodiversity hotspot - Bush, M. B.; Silman, M. R.; Urrego, D. H. (Science, 2004)
A continuous 48,000-year-long paleoecological record from Neotropical lower montane forest reveals a consistent forest presence and an ice-age cooling of ∼5° to 9°C. After 30,000 years of compositional stability, a steady turnover of species marks the 8000-year-long transition from ice-age to Holocene conditions. Although the changes were directional, the rates of community change were no different during this transitional period than in the preceding 30,000-year period of community stability. The warming rate of about 1°C per millennium during the Pleistocene-Holocene transition was an order of magnitude less than the projected changes for the 21st century.
id: 1016

A long pollen record from lowland Amazonia: Forest and cooling in glacial times - Colinvaux, P. A.; DeOliveira, P. E.; Moreno, J. E.; Miller, M. C.; Bush, M. B. (Science, 1996)
A continuous pollen history of more than 40,000 years was obtained from a lake in the lowland Amazon rain forest. Pollen spectra demonstrate that tropical rain forest occupied the region continuously and that savannas or grasslands were not present during the last glacial maximum. The data suggest that the western Amazon forest was not fragmented into refugia in glacial times and that the lowlands were not a source of dust. Glacial age forests were comparable to modern forests but also included species now restricted to higher elevations by temperature, suggesting a cooling of the order of 5 degrees to 6 degrees C.
Vk748Times Cited:350Cited References Count:42